2023
DOI: 10.1017/jfm.2023.412
|View full text |Cite
|
Sign up to set email alerts
|

The effects of boundary proximity on Kelvin–Helmholtz instability and turbulence

Abstract: Studies of Kelvin–Helmholtz (KH) instability have typically modelled the initial flow as an isolated shear layer. In geophysical cases, however, the instability often occurs near boundaries and may therefore be influenced by boundary proximity effects. Ensembles of direct numerical simulations are conducted to understand the effect of boundary proximity on the evolution of the instability and the resulting turbulence. Ensemble averages are used to reduce sensitivity to small variations in initial conditions. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 63 publications
4
6
1
Order By: Relevance
“…In addition, it is apparent that the magnitude of the power spectra increases with turbulence intensity. Figure 5b shows the time evolution of the kinetic energy, KE = KE + KE ′ , where KE = 1 2 U 2 and KE ′ = 1/2 u 2 + v 2 + w 2 where u, v, and w are components of velocity fluctuation in the x, y, and z directions, respectively At t ≈ 0.3 s, the kinetic energy values drop to a local minimum because the Kelvin-Helmholtz's billow structure is partly destroyed, as was also observed by Liu et al [25]. Then, KE increases, suggesting the emergence of turbulence.…”
Section: Effect Of Turbulencesupporting
confidence: 59%
See 1 more Smart Citation
“…In addition, it is apparent that the magnitude of the power spectra increases with turbulence intensity. Figure 5b shows the time evolution of the kinetic energy, KE = KE + KE ′ , where KE = 1 2 U 2 and KE ′ = 1/2 u 2 + v 2 + w 2 where u, v, and w are components of velocity fluctuation in the x, y, and z directions, respectively At t ≈ 0.3 s, the kinetic energy values drop to a local minimum because the Kelvin-Helmholtz's billow structure is partly destroyed, as was also observed by Liu et al [25]. Then, KE increases, suggesting the emergence of turbulence.…”
Section: Effect Of Turbulencesupporting
confidence: 59%
“…Rogers and Moser 1991 [21], Martinez 2006 [22], Soetrisno 1990 [23], and Wang 2016 [24] analyzed 3D KHI simulations. The study of turbulence in relation to KHI has only recently been explored [20,25].…”
Section: Introductionmentioning
confidence: 99%
“…The KHI arises due to the interaction of vorticity waves at two edges of finite shear layers, leading to a sequence of stationary vortex billows that roll up the denser fluids and cause significant mixing (Hazel 1972;Smyth & Peltier 1991;Carpenter et al 2011). However, unlike these previous studies (with the exception of the recent studies (Atoufi et al 2023;Liu, Kaminski & Smyth 2023)) the KHI observed here in the SIC geometry is bounded by no-slip solid boundaries at z = ±1.…”
Section: Kelvin-helmholtz Instabilitycontrasting
confidence: 47%
“…Previous theoretical research on shear instabilities has assumed a single, isolated stratified shear layer (e.g. Caulfield & Peltier 2000;Salehipour & Peltier 2015;Kaminski & Smyth 2019;Lewin & Caulfield 2021;Liu et al 2022Liu et al , 2023, neglecting the potential influence of nearby flow structures. Our goal here is to relax the assumption of a single, isolated shear layer.…”
Section: Introductionmentioning
confidence: 99%